Family Support with Readiness Postpartum Mother Independence - Lili Purnama Sari; Firawati Firawati (Sarana Ilmu Indonesia (salnesia), 2023)
Postpartum or puerperium is a time that every mother will definitely experience. This period lasts 42 days. At this time postpartum mothers experience several changes including physiological changes and psychological changes. The purpose of this study was to see whether there was a relationship between family support and the achievement of postpartum mothers' independence readiness. This research was quantitative research with a cross-sectional study. The sampling technique by means of nonprobability sampling using accidental sampling, the total population of 55 postpartum mothers, and obtained a total sample of 35 people. The instrument used was using a questionnaire to see the support of the mother's family. The questionnaire was filled in by postpartum mothers so that measurements could be carried out objectively. Based on the results of research and discussion, namely that there was a relationship between family support and postpartum mother's independence readiness, this was evidenced from the results of the analysis obtaining p-value=0,001. The importance of educating the family in preparing the mother for independence during the postpartum process is expected to make the mother more prepared to face her role as a mother.